Polyvinyl alcohol/chitosan wound dressings loaded with antiseptics - Massarelli, E. (2022)
Wound care remains a challenge in healthcare. This work aimed to develop a new polyvinyl alcohol (PVA)/chitosan (Ch) based wound dressing able to ensure protection, hydration and a controlled release of antiseptics, as alternative to actual treatments. Two distinct formulations (1:1 and 3:1, w/w) were prepared, sterilized by autoclaving and characterized concerning surface morphology, degradation over the time, mechanical properties and hydrophilicity. Both dressings revealed adequate properties for the intended purpose. The dressings were loaded with chlorhexidine (CHX) and polyhexanide (PHMB) and the drug release profiles were determined using Franz diffusion cells. The release of PHMB was more sustained than CHX, lasting for 2 days. As the amounts of drugs released by PVA/Ch 1:1 were greater, the biological tests were done only with this formulation. The drug loaded dressings revealed antibacterial activity against S. aureus and S. epidermidis, but only the ones loaded with PHMB showed adequate properties in terms of cytotoxicity and irritability. The application of this elastic dressing in the treatment of wounds in a dog led to faster recovery than conventional treatment, suggesting that the material can be a promising alternative in wound care.